BRICs' Philosophies for Development Financing and their Implications for LICs - Yang, Yongzheng; Mwase, Nkunde (Washington, D.C. : International Monetary Fund, 2012)
Flows of development financing from the BRICs (Brazil, Russia, India, and China) to low income countries (LICs) have surged in recent years. Unlike aid from traditional donors, BRICs (excluding Russia) view their financing as primarily based on the principles of South-South cooperation, focusing on mutual benefits without attachment of policy conditionality. This paper provides an overview of the philosophies and modalities of BRIC financing and examines their implications for LIC economies and future LIC-BRIC engagement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet